2013
DOI: 10.1590/s2176-94512013000100010
|View full text |Cite
|
Sign up to set email alerts
|

Occlusal characteristics and orthodontic treatment need in black adolescents in Salvador/BA (Brazil): an epidemiologic study using the Dental Aesthetics Index

Abstract: OBJECTIVE: The objective of this article is to evaluate the need of orthodontic treatment, prevalence and severity of the malocclusions in individuals of black ethnicity in a representative sample of schoolchildren of the city of Salvador/Brazil, as well as to verify if the malocclusion was affected by socio-demographic conditions such as age and gender. METHODS: The reference population was constituted of schoolchildren with age between 12 and 15 years, enrolled in public and private schools. The malocclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 11 publications
2
9
0
4
Order By: Relevance
“…In the current sample, the most frequent malocclusion was crowding, which was found in 34.4% of the cases and is within the range reported by other studies -18.05% to 87% [18][19][20][21] . This prevalence was already expected because, according to Peres 9 , such malocclusion is most often associated with Class I molar relationship.…”
Section: Discussionsupporting
confidence: 89%
“…In the current sample, the most frequent malocclusion was crowding, which was found in 34.4% of the cases and is within the range reported by other studies -18.05% to 87% [18][19][20][21] . This prevalence was already expected because, according to Peres 9 , such malocclusion is most often associated with Class I molar relationship.…”
Section: Discussionsupporting
confidence: 89%
“…The main occlusal traits found in patients who had a great need for orthodontic treatment were open bite, increased overjet, and overbite. Comparable findings were reported among Brazilian patients with great need for orthodontic treatment 41. Further, it was reported that the most common occlusal traits among Saudi children requiring orthodontic treatment were tooth displacement, increased overjet, and deep bite 28.…”
Section: Discussionmentioning
confidence: 74%
“…Studies performed in the United Kingdom, 23 Nigeria, 24 and Croatia 25 have shown low levels of self-perceived need for orthodontic treatment (6%, 17.5%, and 24,2%, respectively), suggesting the existences of differences related to ethnic and cultural factors. 9 Conceptions of beauty vary widely among cultures, with a beautiful body associated with intelligence and high income in Western societies; this factor explains why Brazilians, especially adolescents, pay so much attention to cosmetic factors. 26 We have found a correlation between normative and self-perceived needs for orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Orthodontists appear to be in consensus that parameters constituting morphological normality can vary among ethnic groups or populations from different geographic regions. 9 Together with these ethnic aspects, socioeconomic factors must be considered in the examination of occlusion; this aspect of orthodontics should be studied within a social context, given the importance not only of the physical consequences of poor development, but also its negative impact on social well-being. 5,10 With the development of more comfortable and esthetic orthodontic devices, improved treatment, and more widespread access to information, patients' perceptions about whether their occlusion is cosmetically acceptable have changed.…”
Section: Declaration Of Interestsmentioning
confidence: 99%